Developing a Consistent Database for Regional Geologic CO2 Storage Capacity Worldwide. (July 2017) - Kearns, Jordan; Teletzke, Gary; Palmer, Jeffrey; Thomann, Hans; Kheshgi, Haroon; Chen, Yen-Heng Henry; Paltsev, Sergey; Herzog, Howard
Abstract: Assessments of the geologic storage capacity of carbon dioxide in the current literature are incomplete and inconsistent, complicating efforts to assess the worldwide potential for carbon dioxide capture and storage (CCS). We developed a method for generating first-order estimates of storage capacity requiring minimal data to characterize a geologic formation. We show this simplified method accounts for the majority of the variance in storage capacity found in more detailed studies conducted in the United States. We apply our method to create a worldwide database of storage capacity, disaggregated into 18 regions, and compare this storage capacity to CCS deployment in the MIT Economic Prediction and Policy Analysis (EPPA) model. Globally, we estimate there are between 8, 000 and 55, 000 gigatonnes (Gt) of practically accessible geologic storage capacity for carbon dioxide. For most of the regions, our results indicate storage capacity is not a limiting factor for CCS deployment through the rest of this century even if stringent emissions reductions are required.